Hak Memilih Tuna Aksara Pada Pelaksanaan Pemilu Serentak 2019 Di Kota Singkawang - Saliro, Sri Sudono; Akadol, Jamiat; Rachman, Saiful; Setiawan, Agus (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2020)
The purpose of this study, among others, first, is to analyze the laws and regulations concerning the right to choose illiterates in the 2019 simultaneous elections in the City of Singkawang. Second, for the evaluation of the legal aspects of the Election, specifically talking about the substance of the contents of the laws and regulations concerning providing assistance to illiterate voters. Third, to remind us together that the issue of the right to choose illiterates is an important issue that must be regulated in the election laws and regulations. The focus of the study in this paper is related to how to provide assistance to illiterate voters in the implementation of the 2019 simultaneous elections in Singkawang City. This research is a field research using descriptive qualitative method, meaning that the writer is directly involved with the resource person to reveal the social reality in the community. To obtain data the authors conducted observations and interviews. The findings can be concluded that illiterate voters cannot be provided with assistance when voting on the 2019 simultaneous elections in Singkawang City because there is no legal basis governing the provision of assistance to illiterate voters. So that the impact of the lack of legal basis, illiterate voters who come to polling stations and enter the voting booths, do not vote because of the confusion of the voters themselves.Keywords: Right to Choose, Illiteracy.